Pengaruh Motivasi Kerja Dan Kompensasi Pegawai Terhadap Kinerja Pegawai Di Kantor Camat Mapilli Kabupaten Polewali Mandar: The Influence Of Work Motivation And Employee Compensation On Employee Performance At The Mapilli District Office Polewali Mandar Regency - Nur Qamariah; Arifhan Ady Dj (Journal of Economic, Public, and Accounting (JEPA), 2026)
This study aims to analyze the effect of work motivation and compensation on employee performance. The type of research used is descriptive quantitative. The population of this study consists of all employees at the Mapilli Subdistrict Office, totaling 33 respondents, comprising 18 civil servants and 15 honorary employees. Data were collected through observation, questionnaires, interviews, and documentation. The data analysis technique employed was multiple linear regression analysis, including validity and reliability tests, classical assumption tests, t-test, F-test, and coefficient of determination (R²), using SPSS version 24. The results indicate that work motivation has a significant effect on employee performance, compensation also has a significant effect on employee performance, and simultaneously, work motivation and compensation significantly influence employee performance. The coefficient of determination (R²) of 89.7% shows that variations in employee performance can be explained by work motivation and compensation, while the remaining 10.3% is influenced by other variables not included in this study.